Eosinophil Count and Neutrophil-Lymphocyte Count Ratio as Prognostic Markers in Patients with Bacteremia: A Retrospective Cohort Study - Terradas, Roser (Public Library of Science, 2012)
INTRODUCTION: There is scarce evidence on the use of eosinophil count as a marker of outcome in patients with infection. The aim of this study was to evaluate whether changes in eosinophil count, as well as the neutrophil-lymphocyte count ratio (NLCR), could be used as clinical markers of outcome in patients with bacteremia. METHODS: We performed a retrospective study of patients with a first episode of community-acquired or healthcare-related bacteremia during hospital admission between 2004 and 2009. A total of 2,311 patients were included. Cox regression was used to analyze the behaviour of eosinophil count and the NLCR in survivors and non-survivors. RESULTS: In the adjusted analysis, the main independent risk factor for mortality was persistence of an eosinophil count below 0.0454·10(3)/uL (HR = 4.20; 95% CI 2.66–6.62). An NLCR value >7 was also an independent risk factor but was of lesser importance. The mean eosinophil count in survivors showed a tendency to increase rapidly and to achieve normal values between the second and third day. In these patients, the NLCR was <7 between the second and third day. CONCLUSION: Both sustained eosinopenia and persistence of an NLCR >7 were independent markers of mortality in patients with bacteremia.